Manufacturing architecture : An architect's guide to custom processes, materials, and applications - Gulling, Dana K. (London Laurence King Publishing, 2018)
Computer-aided design has greatly expanded the opportunities for architects to create innovative buildings with custom components. While most architects were exposed to CAD when they were students, few of them have in-depth knowledge or experience with using it to customize repetitive manufacturing processes. This book provides designers of all levels with all the information they need to make the most of the exciting opportunities offered by custom manufacturing.
Keywords: MODELS, SITE PLANNING, DRAWINGS (AR-DRW)